Role of Social Media Marketing on Customer Purchase Intention in Kathmandu Valley Nepal - Ballav Niroula; Sapana Vaidya (Journal of Islamic Economics Perspectives, 2025)
How Consumer Purchase Intentions are affected by Social Media Marketing (with a specific reference to Kathmandu Valley) This research is restricted to examining the correlation between social media marketing and consumer purchase intention, as well as providing an analysis of the impact of social media marketing on consumer buy intention. In order to determine the relationship between social media marketing and consumer purchase intention, two social media advertising campaigns have been examined using a quantitative research methodology as a basis for a casual comparative analysis. Only 350 respondents completed the 382 questionnaires that were distributed using Google Form Sharing, which is how the data utilised in this study were gathered. A five-point Likert scale base questionnaire for the variables is one of the sets of instruments put up for the study, along with demographic and general information questions for each of the three groups. These kinds of techniques are not the ideal choice, and quantitative research makes this clear when convenience or purposeful sampling is used to collect data (Yilmaz, 2013). Analysing Data. The coefficient of variation and Pearson's correlation were the two methods used to analyse the data. Conversely, whereas informativeness and buy intention have the most positive correlation with one another, perceived relevance and purchase intention have the lowest correlation. Purchase Intention is the dependent variable, and the five variables (Habit, Informativeness, Interactivity, Performance Expectancy, and Hedonic Motivation) have p-values less than 0.05, indicating that they positively influence it. In contrast, Perceived Relevance has a p-value greater than 0.05, indicating that it has no significant effect on Purchase Intention. Many stakeholders, including but not limited to marketers, business experts, and policy officials in developing nations like Nepal, benefit from this study. The results offer practical insights into how we might use various social media marketing elements to increase customer buy intentions.